Generation of late-born neurons in the ventral spinal cord requires the coordination of retinoic acid and Notch signaling. (18th August 2015) - Ryu, Jae-Ho; Kong, Hee Jeong; Park, Jung Youn; Lim, Kyung-Eun; An, Cheul Min; Lee, Jehee; Yeo, Sang-Yeob
Abstract: Neural progenitor cells generate various types of neurons and glia in a tightly regulated manner. During primary neurogenesis, retinoic acid (RA) acts earlier than Notch signaling and regulates differentiation and proliferation by upregulating proneural and neurogenic genes in the neural plate. However, the relationship between Notch signaling and the retinoid pathway during late neurogenesis remains unclear. We investigated the role of Mindbomb (Mib)-mediated Notch signaling in the differentiation of neural progenitors during late neurogenesis by overexpressing Mib and administering RA to Tg[hsp70-Mib:EGFP] . The majority of cells in the p3 domain differentiated into GABAergic Kolmer–Agduhr (KA) cells in Tg[hsp70-mib:EGFP] embryos heat-shocked during late neurogenesis, whereas these phenotypes were suppressed by exogenous RA. Our observations suggest that Mib-mediated Notch signaling plays a critical role in the temporal differentiation of neural progenitors, and that the generation of late-born KA″ cells is regulated by the interplay between Mib and RA.